ETHICAL VISION OF THE QUR’AN (Interpreting Concept of the Qur’anic Sociology in Developing Religious Harmony) - MK Ridwan; Siti Robikah (Islam Futura, 2019)
This paper aims to provide a perspective of sociology of the Qur’an in the development of religious harmony. This thought was motivated by a phenomenon in which Islam appears with a hardened face. The syndrome of Islamic populism shows an Islamic conservative turn and tends to prioritize formal and normative values in practise. This model is wholly vulnerable causing conflicts both intra and inter-religious. Its exclusive, binary, and aggressive style make Islam inhospitable to the plurality of groups, religions, and cultures. This model of Islam needs to be returned to its face which is inclusive, ecumenical and accommodating to diversity based on the values of the Qur'an. So this agenda requires reformulation of Islamic doctrines that have been considered established. In conclusion, this study argues that although the Qur'an supports the agenda of mission activities, it compulsively requires a dialogic-communicative process. Thus, the Qur'an's greatest contribution to the development of harmonization of diverse people lies in its inclusive and accommodating character to diversity. The principles developed by the Qur’an can be covered through various approaches, both sociological and theological. Sociologically, the Qur'an encourages humanity to jointly declare universal values in every religious activity. These values become the basis of the necessity of each religious community to be willing and able to create a space of togetherness and dialogue to formulate humanitarian agendas. Theologically, the Qur’an does not erase pre-Islamic religions implying that the Qur’an supports diversity and commands humans to always compete in the framework of goodness (religion).